Postgraduate training in audiology improves clinicians' audiology-related cue utilisation. (2nd September 2018) - Watkinson, Jarrah; Bristow, Grant; Auton, Jaime; McMahon, Catherine M.; Wiggins, Mark W.
Abstract: Objective: This study was designed to test whether cue utilisation might be employed as a tool to assess the diagnostic skills of audiologists. The utilisation of cues is a characteristic of expertise and critical for successful diagnoses in clinical settings. However, neither in training nor in practice, is there a means by which the diagnostic skills of audiologists can be assessed objectively and reliably. Design: The study comprised a pre-post training evaluation, controlling for prior exposure to the diagnostic testing tool. Study sample: Three cohorts of trainee audiologists were evaluated, one of which was tested prior to, and following a two-year training programme (16 participants), while the other two groups acted as controls (23 participants and 20 participants, respectively). Results: Consistent with expectations, cue utilisation increased from the initial to the final stages of training and this effect could not be attributed to cohort nor learning effects. Conclusions: At an applied level, the outcomes provide the basis for a cue-based diagnostic assessment tool that can provide both trainee and practising audiologists with detailed feedback concerning their diagnostic skills.